The effect of once-off tillage on selected soil physical and chemical properties and resultant crop response on a shale derived soil under no-till in the Swartland sub-region of the Western Cape - Leygonie, Izane Riana (Sellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.